2013
DOI: 10.1016/j.celrep.2013.09.013
|View full text |Cite
|
Sign up to set email alerts
|

TAFA4, a Chemokine-like Protein, Modulates Injury-Induced Mechanical and Chemical Pain Hypersensitivity in Mice

Abstract: C-low-threshold mechanoreceptors (C-LTMRs) are unique among C-unmyelinated primary sensory neurons. These neurons convey two opposite aspects of touch sensation: a sensation of pleasantness, and a sensation of injury-induced mechanical pain. Here, we show that TAFA4 is a specific marker of C-LTMRs. Genetic labeling in combination with electrophysiological recordings show that TAFA4+ neurons have intrinsic properties of mechano-nociceptors. TAFA4-null mice exhibit enhanced mechanical and chemical hypersensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
156
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(164 citation statements)
references
References 30 publications
7
156
0
1
Order By: Relevance
“…The fact that the presynaptic cell in the pairs consistently showed lower thresholds and slower dorsal root evoked excitatory post synaptic potentials (EPSPs) than the postsynaptic neuron was consistent with the notion that the dorsal root excitation was associated with relatively large diameter rapidly conducting C-LTMs while the postsynaptic cell was in receipt of c-nociceptive inputs (Lu and Perl, 2003). Further support for the notion that C-LTM inputs can supress nociceptive impulses comes from the observation that administration of TAFA4, a chemokine protein and specific marker on C-LTMs, reduced inflammation induced mechanical hypersensitivity (Delfini et al, 2013). In contrast, TAFA4 knockout mice displayed enhanced mechanical hypersensitivity following inflammation or injury which could be reversed by administration of TAFA4 protein into the spinal cord (Delfini et al, 2013).…”
Section: C-tactile Afferents Inhibit Painsupporting
confidence: 68%
See 1 more Smart Citation
“…The fact that the presynaptic cell in the pairs consistently showed lower thresholds and slower dorsal root evoked excitatory post synaptic potentials (EPSPs) than the postsynaptic neuron was consistent with the notion that the dorsal root excitation was associated with relatively large diameter rapidly conducting C-LTMs while the postsynaptic cell was in receipt of c-nociceptive inputs (Lu and Perl, 2003). Further support for the notion that C-LTM inputs can supress nociceptive impulses comes from the observation that administration of TAFA4, a chemokine protein and specific marker on C-LTMs, reduced inflammation induced mechanical hypersensitivity (Delfini et al, 2013). In contrast, TAFA4 knockout mice displayed enhanced mechanical hypersensitivity following inflammation or injury which could be reversed by administration of TAFA4 protein into the spinal cord (Delfini et al, 2013).…”
Section: C-tactile Afferents Inhibit Painsupporting
confidence: 68%
“…Further support for the notion that C-LTM inputs can supress nociceptive impulses comes from the observation that administration of TAFA4, a chemokine protein and specific marker on C-LTMs, reduced inflammation induced mechanical hypersensitivity (Delfini et al, 2013). In contrast, TAFA4 knockout mice displayed enhanced mechanical hypersensitivity following inflammation or injury which could be reversed by administration of TAFA4 protein into the spinal cord (Delfini et al, 2013). Taken together these findings are consistent with an analgesic role for C-LTMs via their modulation of nociceptive inputs to the spinal cord.…”
Section: C-tactile Afferents Inhibit Painmentioning
confidence: 99%
“…This higher variability, as compared to nociceptive C-fibres, was unexpected, as we hypothesised that VGluT3 + fibres would be a more homogenous group than the large populations of peptidergic and non-peptidergic C-fibres that were electrically stimulated in VGluT3 −/− mice. However, a recent study also reported heterogeneous responses in putative C-LTMRs upon application of hypo-osmotic solution or a TRPA1-receptor agonist [12]. The response variability observed by us and others may reflect functional heterogeneity or the existence of further not yet identified subpopulations of VGluT3 + A- and C-fibres.…”
Section: Discussionmentioning
confidence: 57%
“…In conclusion, our work identifies FAM19A4 as a novel cytokine ligand of FPR1 in macrophages for the first time. However, Delfini et al 38 have defined FAM19A4 to be a specific marker of the C-low-threshold mechanoreceptor, which could be a potent analgesic in pain relief. FPR1 is not restricted to leukocytes involved in inflammatory responses toward infection, but is also found on the cells of the neuromuscular and endocrine system.…”
Section: Fpr1 Is a Functional Receptor Of Fam19a4mentioning
confidence: 99%